Approximation of classes C_∞ ^ψ by zygmund sumsby zygmund sums - Fedorenko, An. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We consider the approximation of functions of the classes of ψ by Zygmund sums. In papticular, we present asymptotic equalities for the quantities ε _n (C_∞ ^ψ ;Z_n )_C under various conditions imposed on functions ψ_1(·) and ψ_2(·).